Structure and evolutionary history of DISC1. - Sanchez-Pulido, L; Ponting, C (2011)
Evolutionary and protein structural analyses can provide functional insights into genes implicated in human psychiatric diseases. Even eukaryotic organisms lacking nervous systems contain homologues of many key signalling molecules of animal neurons implying that human cognition derives, in part, from modifications of ancestral molecules and complexes. One protein whose evolutionary origin is obscure is DISC1 (disrupted in schizophrenia 1) whose gene locus has been associated with many psychiatric conditions including schizophrenia, clinical depression and bipolar disorder. This protein's rapid evolution and its unusual amino acid and α-helix composition have hindered searches for DISC1 homologues in species other than vertebrates. Here, we review the evolution and structure of the DISC1 protein in the light of in-depth sequence analyses. These predict DISC1 orthologues in diverse eukaryotic organisms, including early-branching animals such as amphioxus, sea anemone, amoebas and Trichoplax, and in plants and algae. DISC1 thus is widespread among eukaryotes, although it remains absent from fungi, nematodes and Diptera, including fruit flies. These observations now permit studies of DISC1 function in simple non-vertebrate model organisms. Surprisingly, these analyses also identify between two and four sequence repeats in DISC1 orthologues. The first two of these repeats show significant sequence similarity to the UVR family of globular domains. These UVR-like repeats are predicted to contain, not coiled coil structures, but rather two closely associated antiparallel α-helices. One common missense variant in DISC1 (L607F) lies within the second DISC1 UVR-like domain. These observations should assist in delineating the functional regions of the DISC1 protein.